Analisis Isi Pemberitaan tentang Pemerkosaan pada Portal Berita Online - Lisa Adelin Putri; S Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The writing of news articles on rape cases requires careful attention in order to respect the traumatic experiences of the victims and avoid negative perceptions of rape victims. Despite journalists having a moral and ethical foundation in carrying out their duties, news coverage of rape cases by online news portals often comes under scrutiny from the public for frequently violating these principles. This research employs quantitative content analysis, aiming to provide objective data on the tendencies of online news websites in Indonesia when reporting rape cases. The data was obtained from a total of 300 news articles published by 10 popular online news websites in Indonesia from January 1, 2020, to October 31, 2021. The findings of this study demonstrate that sensational headlines commonly used by Indonesian news websites were characterized by clickbait and emotionally driven words. The use of images in reporting on rape cases refrains from disclosing the identities of both victims and underage perpetrators, while also avoiding explicit visuals. In terms of the body of the news articles, the titles and content are generally relevant. Nearly all the examined news websites have at some point included information or statements that could give rise to prejudice and discrimination against rape victims. Among the total sample studied, 9% of the articles contained narratives with biased and discriminatory tones. The description of rape incidents frequently employs neutral terminology accompanied by euphemistic replacements for the term